2015
DOI: 10.1103/physrevb.92.115433
|View full text |Cite
|
Sign up to set email alerts
|

Quantum anomalous Hall effect in graphene coupled to skyrmions

Abstract: Skyrmions are topologically protected spin textures, characterized by a topological winding number N , that occur spontaneously in some magnetic materials. Recent experiments have demonstrated the capability to grow graphene on top Fe/Ir, a system that exhibits a two-dimensional skyrmion lattice. Here we show that a weak exchange coupling between the Dirac electrons in graphene and a two-dimensional skyrmion lattice with N = ±1 drives graphene into a quantum anomalous Hall phase, with a band gap in bulk, a Che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
0
34
1
Order By: Relevance
“…We have also found that the sign of the Chern number is controlled by the sign of the applied magnetic field. Changing the sign of D results in a change of the skyrmion winding numbers, but it does not change the sign of the spin-wave Chern numbers, in contrast with the case of the electronic Chern number in a skyrmion lattice [47].…”
Section: Topological Magnonic Bandsmentioning
confidence: 92%
“…We have also found that the sign of the Chern number is controlled by the sign of the applied magnetic field. Changing the sign of D results in a change of the skyrmion winding numbers, but it does not change the sign of the spin-wave Chern numbers, in contrast with the case of the electronic Chern number in a skyrmion lattice [47].…”
Section: Topological Magnonic Bandsmentioning
confidence: 92%
“…In the following and especially in the last 20 years it has been found that the external magnetic field is not mandatory to produce a Hall effect and can be exchanged for example by spin-orbit coupling [2] or a chiral magnetic texture [3] that produces an effective magnetic field, that is a "Berry curvature" [4]. The family of Hall effects for electrons in solids was extended by the quantum Hall effect [5][6][7], anomalous Hall effect [2], quantum anomalous Hall effect [8,9], spin Hall effect [10,11], quantum spin Hall effect [12,13], and topological Hall effect [3,[14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The < i, j > symbol implies summation over all nearest neighboring pairs of atoms, and we are assuming that the magnitude of the magnetization is uniform over the whole graphene lattice. This Hamiltonian has been considered before 23 for the case of 2D graphene interacting with a skyrmion crystal. In contrast, here we consider a graphene device that hosts an individual skyrmion.…”
Section: Tight-binding Quantum Transport Approachmentioning
confidence: 99%